Phase Transformation, Microstructures, and Mechanical Properties of α + β Two-Phase Titanium Alloy Deposited Metal by Surfacing Welding - Naiwen Fang; Ruisheng Huang; Kai Xu; Tianli Zhang; Pengbo Wu; Yiming Ma; Hao Cao; Jian Qin; Jipeng Zou (Advances in Materials Science and Engineering)
The effect of cooling rate on phase transformation, microstructures, and mechanical properties of TC4 titanium alloy deposited metal by laser surfacing welding with filler wire was investigated by in situ observation with a high-temperature laser confocal microscope, XRD, SEM, and through microhardness test. The results showed that primary α phase began to appear at grain boundaries when the deposited metal was heated to 890.5°C, and microstructures were all composed of coarse β columnar grains after the temperature was raised to 1 190.2°C; with the increase of cooling rate during the cooling process, temperature for starting new phase transformation decreased from 943.7°C to 811.1°C, and temperature for ending the transformation increased gradually from 708.0°C to 736.2°C; when cooled to room temperature at a rate of 1°C/s, microstructures consisted of α phase; at a rate of 15°C/s, acicular α′ martensite appeared in the microstructures; at 100°C/s, the microstructures were completely comprised by acicular α′ martensite; when the cooling rate was low, V element would be slightly precipitated from αgb into the matrix; when cooling turned faster, V element had no time to enter the matrix by diffusion, so it became uniformly distributed; as the cooling rate getting faster, lamellar microstructures became thinner gradually, and microhardness of the deposited metal was improved in a gradual manner.